2017
DOI: 10.1371/journal.ppat.1006103
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Is an Innate Mechanism Associated with Leprosy Polarization

Abstract: Leprosy is a chronic infectious disease that may present different clinical forms according to the immune response of the host. Levels of IFN-γ are significantly raised in paucibacillary tuberculoid (T-lep) when compared with multibacillary lepromatous (L-lep) patients. IFN-γ primes macrophages for inflammatory activation and induces the autophagy antimicrobial mechanism. The involvement of autophagy in the immune response against Mycobacterium leprae remains unexplored. Here, we demonstrated by different auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 72 publications
1
93
0
Order By: Relevance
“…As mentioned earlier, the paucibacillary tuberculoid skin macrophages activate the vitamin D pathway and produce antimicrobial peptides that could be involved in autophagy induction. In addition, Silva and colleagues [58] demonstrated that autophagy is differentially regulated between leprosy polar forms. In paucibacillary tuberculoid skin lesion macrophages, IFN-γ/beclin 1-induced autophagy contributes for M. leprae control, whereas in lepromatous macrophages B cell lymphoma 2 (BCL2)-mediated blockade of beclin 1 autophagic pathway promotes mycobacterial persistence [58].…”
Section: The Role Of Macrophages In the Immune Response To M Lepraementioning
confidence: 99%
See 4 more Smart Citations
“…As mentioned earlier, the paucibacillary tuberculoid skin macrophages activate the vitamin D pathway and produce antimicrobial peptides that could be involved in autophagy induction. In addition, Silva and colleagues [58] demonstrated that autophagy is differentially regulated between leprosy polar forms. In paucibacillary tuberculoid skin lesion macrophages, IFN-γ/beclin 1-induced autophagy contributes for M. leprae control, whereas in lepromatous macrophages B cell lymphoma 2 (BCL2)-mediated blockade of beclin 1 autophagic pathway promotes mycobacterial persistence [58].…”
Section: The Role Of Macrophages In the Immune Response To M Lepraementioning
confidence: 99%
“…In addition, Silva and colleagues [58] demonstrated that autophagy is differentially regulated between leprosy polar forms. In paucibacillary tuberculoid skin lesion macrophages, IFN-γ/beclin 1-induced autophagy contributes for M. leprae control, whereas in lepromatous macrophages B cell lymphoma 2 (BCL2)-mediated blockade of beclin 1 autophagic pathway promotes mycobacterial persistence [58]. Indeed, the M. leprae can take advantage of host antiviral protein 2′-5′-oligoadenylate synthetase like (OASL) to inhibit autophagy and promote its own survival through a stimulator of interferon genes (STING)-mediated type I IFN response [60].…”
Section: The Role Of Macrophages In the Immune Response To M Lepraementioning
confidence: 99%
See 3 more Smart Citations